(untitled) (Cadernos de Psicologia Social do Trabalho, 2007)
This essay aims to present a pilot project of action towards unemployed people, developed in the Center of Psychology Applied to Work of the Institute of Psychology of Universidade de São Paulo. In the first part of the article, it is done a brief presentation of the context of project elaboration and are approached the theoretical conceptions that guided the proposal. In the second part, are brought: project objectives and group characterization, methodological design, description, and analysis of each meeting. The pilot project was aimed to men and women unemployed aged over 24, living in the metropolitan region of São Paulo, through a group work with 10 people, summing seven meetings. This proposition aimed the constitution of a place for reflection and experience exchange among the participants not only about the unemployment, but also the repercussions and ways to deal with it and about their life and work trajectories and limits and possibilities and personal and social strategies for income and work generation.